2010
DOI: 10.4323/rjlm.2010.25
|View full text |Cite
|
Sign up to set email alerts
|

Fahr's disease: bilateral symmetrical striopallidodentate calcification

Abstract: Fahr's disease refers to rare syndrome characterised by symmetrical and bilateral intracranial calcification. This disease refers to a sporadic or familial idiopathic calcification of the basal ganglia that may lead to neurological, psychiatric, and cognitive abnormalities. The origin and pathomechanism of this disorder are unknown, and is the reason why other cases with basal ganglia calcification remain asymptomatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…According to Hecser, the majority of Fahr's patients present between the fourth and sixth decades of life; however, the onset of symptoms in younger patients (as in our patient) and children is not rare (10). Although the parents admitted to noticing the abnormal behavior and mentality of their daughter at the age of 19 years, careful questioning and history taking from her siblings uncovered poor social interaction, non-participation in family events, avoiding everyday house and farm activities, and insomnia starting around the age of 11 years.…”
Section: Case Presentationmentioning
confidence: 54%
“…According to Hecser, the majority of Fahr's patients present between the fourth and sixth decades of life; however, the onset of symptoms in younger patients (as in our patient) and children is not rare (10). Although the parents admitted to noticing the abnormal behavior and mentality of their daughter at the age of 19 years, careful questioning and history taking from her siblings uncovered poor social interaction, non-participation in family events, avoiding everyday house and farm activities, and insomnia starting around the age of 11 years.…”
Section: Case Presentationmentioning
confidence: 54%
“…Cases presenting emotional lability or progressive changes in personality and behavior, without parkinsonian features, have been described (Lam et al, 2007). Other neu-rological features are seizures, syncope or stroke-like events, and frontal-subcortical patterns of behavior (Hecser, Croitorescu, Siklodi, & Jung, 2010). Importantly, psychiatric symptoms such as psychosis, mood disorders, personality changes, anxiety and apathy are common (López-Villegas et al, 1996), and they were present at onset in several cases (Calabrò, Spadaro, Marra, & Bramanti, 2014;Gülsün, Baykiz, Kabatas ¸, & Belli, 2006).…”
mentioning
confidence: 99%
“…[12] FD is a clinically heterogeneous condition and may manifest in the form of a broad range of psychiatric, cognitive impairments, and neurological features. [3] FD needs to be differentiated from Fahr's syndrome, where similar clinical features are produced by underlying preexisting diseases.…”
mentioning
confidence: 99%
“…Fahr's disease (FD) is commonly called as idiopathic basal ganglia calcification and it was found that lateral thalamus, dentate nucleus of cerebellum as well as the frontal cortex also get affected as the disease progresses. [ 1 2 ] FD is a clinically heterogeneous condition and may manifest in the form of a broad range of psychiatric, cognitive impairments, and neurological features. [ 3 ] FD needs to be differentiated from Fahr's syndrome, where similar clinical features are produced by underlying preexisting diseases.…”
mentioning
confidence: 99%